(untitled) (Baghdad Science Journal, 2024)
In this study, the optical characteristics of polyvinyl chloride(PVC), polyvinyl alcohol (PVA) and binary PVA - PVC blend films at various concentrations PVA75% + PVC25%, PVA50% + PVC50%, and PVA25% + PVC 75% are examined in relation to temperature variations 25, 120 and 140 °C for 1 hour. The binary blend films of polyvinyl chloride and polyvinyl alcohol were produced using casting techniques. UV-visible spectroscopy used to determine the optical properties of the films in the wavelength range (200-900) nm, such as transmittance, absorbance, absorption coefficient and energy gap as well as the impact of temperature on these parameters, were measured and examined. The results of the experimental part demonstrated that the absorption and absorption coefficient of binary PVA - PVC blend films at various concentrations increased with increased concentration of polyvinyl alcohol (PVA) polymer. The energy gap of binary PVA-PVC blend films at various concentrations decreased with increased concentration of polyvinyl alcohol (PVA). The ratio of (PVA 75%+ PVC25%) binary blend has extremely suitable optical characteristics. The absorption and absorption coefficient of binary PVA-PVC blends increased with increased temperatures. While the transmission and energy gap of binary PVA-PVC blend films were decreased as the temperature was raised. The nature of electronic transitions of binary PVA - PVC blend films at various concentrations before and after exposure to temperatures is indirect. From the results obtained from the experimental part, it concludes that the absorption and absorption coefficient of binary PVA - PVC blend films are better than pure polyvinyl chloride and polyvinyl alcohol polymers. The optical characteristics of binary PVA - PVC blend films effect by exposure to temperatures.